Analysis of Green Consumer Behavior on Purchasing Waste Recycling Products Reviewed from Environmental Knowledges, Recycle Behavior, and Government Regulations - Leonard, Natassya Adelia Candradhita; Meilina, Restin (MSJ : Majority Science Journal, 2024)
Indonesia is the second largest producer of waste after China with an estimated 0.48-1.29 million metric tons per year. Based on data from the Environment, Hygiene and Landscaping Agency (DLHKP), as of 2022 the Klotok Final Management Site (TPA) receives as much as 140 tons of waste per day, the waste is included in organic waste and inorganic waste. Meanwhile, inefficient waste handling can cause water quality in an area to be very poor and contain toxic waste and garbage that is allowed to accumulate can cause flooding and endanger public health. One of the community organizations that cares about waste processing is the Melati Waste Bank in Kediri City. The Melati Waste Bank is productive in carrying out activities to reduce waste in Kediri City, this is evidenced by the process of sorting waste, processing sorted waste, then distribute the product into the society. Unfortunately the efforts are under the expectations of the management and volunteers of the Melati Waste Bank are due to lack of interest in purchasing waste recycling products. This research uses qualitative methods using triangulation techniques where research is carried out by interviews. So as to obtain the results that consumer behavior in purchasing waste recycling products is based on environmental knowledges, recycle behavior and government regulations related to restrictions on the use of single-use plastics.